UTILIZATION OF MORINGA LEAVES AS A LOCAL FOOD INNOVATION TO REDUCE STUNTING IN BULURI SUBDISTRICT, PALU CITY - Syahrir, Muhammad Sabri; Hilintang, Rendhar Putri; Kamilah, Ummu; Irianingtyas, Riza (Community Service Journal of Indonesia, 2024)
Stunting is a serious issue affecting child growth and development due to chronic malnutrition and recurrent infections. In Palu City, the prevalence of stunting among children under five reached 22.1% in 2023, with a target to reduce it to 14% by 2024. Achieving this target requires a comprehensive approach, including public education on the importance of stunting prevention and balanced nutrition. In addition to education, training in healthy food processing based on local food potential is also conducted, aimed at utilizing local resources rich in nutritional value. This program is implemented through step-by-step cooking demonstrations with direct community involvement. One of the food innovations introduced is the processing of moringa leaves into moringa chicken tofu balls, which are nutrient-dense to support child growth. The program has shown improvements in community knowledge and skills in processing local foods and understanding nutritional intake. However, the program has not fully achieved its target due to low awareness among mothers about balanced nutrition. Therefore, additional strategies are needed, such as continuous nutrition campaigns, strengthening community participation, and cross-sector collaboration to achieve optimal results.